Data compilation of bio-SiO2 MAR from 21 sites - Xinying Wu; Yue Hu; Jingbo Nan; Weiqi Yao (PANGAEA, 2024)
The table includes complicated bio-SiO2 MAR from 21 sites in the global ocean during the late Miocene. We also use Geologic Time Scale 2020 timescale (Gradstein et al., 2020; doi:10.1016/C2020-1-02369-3) to re-calculate the ages of other sites for the bio-SiO2 MAR compilation. We calculate mass accumulation rate (MAR) as a function of linear sedimentation rate (cm/ka) and dry bulk density (g/cm^3). The accumulation rates of bio-SiO2 are calculated as the product of MAR and the weight percent of biogenic SiO2 (wt%) in sediments.
In: Wu, X et al. (2024): Multi-proxy reconstructions of productivity during the late Miocene [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.973162